EFEKTIVITAS MODUL TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI MEDAN MAGNET KELAS XI DI SMK SATRIA BHAKTI NGANJUK - Eki Luthfintri (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2016)
ABSTRACTThe times are getting faster and powerful impact on the changes in all fields. One in the field of education which requires students to improve the mastery of a concept. Efforts to support it, it is used in the form of learning media modules. This study aims to determine the effect of learning modules for students' mastery of concepts. This research is a kind of experimental research design with posttest only control design with a sample of 2 XI where samples taken by random sampling technique. The data was normally distributed through the test of normality (Kolmogorov-Smirnov test in SPSS 20) equal 0,654 significantion 0,786 (experiment class) dan 0,619 significantion 0,839 (control class) and homogeneous through the test of homogeneity (Levene's test in SPSS 20) for 0,025 significantion 0,874 . Posttest t test results which is obtained tmeasure> ttable to 5%. The research proves that the use of the module in the learning activities can improve students' mastery of concepts. Module development should be increased and combined with other learning models. KEYWORDS: module, achievement, the magnetic field